14m-3=7m+6-2n

Simple and best practice solution for 14m-3=7m+6-2n equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 14m-3=7m+6-2n equation:


Simplifying
14m + -3 = 7m + 6 + -2n

Reorder the terms:
-3 + 14m = 7m + 6 + -2n

Reorder the terms:
-3 + 14m = 6 + 7m + -2n

Solving
-3 + 14m = 6 + 7m + -2n

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '-7m' to each side of the equation.
-3 + 14m + -7m = 6 + 7m + -7m + -2n

Combine like terms: 14m + -7m = 7m
-3 + 7m = 6 + 7m + -7m + -2n

Combine like terms: 7m + -7m = 0
-3 + 7m = 6 + 0 + -2n
-3 + 7m = 6 + -2n

Add '3' to each side of the equation.
-3 + 3 + 7m = 6 + 3 + -2n

Combine like terms: -3 + 3 = 0
0 + 7m = 6 + 3 + -2n
7m = 6 + 3 + -2n

Combine like terms: 6 + 3 = 9
7m = 9 + -2n

Divide each side by '7'.
m = 1.285714286 + -0.2857142857n

Simplifying
m = 1.285714286 + -0.2857142857n

See similar equations:

| 15(X)(X+2)=2145 | | 4(-9)-70= | | 2x-6=x-3(2-x) | | -7-x=x-9 | | 44-7p=30 | | 4x-9-70= | | 7(2a+1)=14p+7 | | -20=25p | | 5-(x-3)=25 | | A-2ab=-10 | | 0.75x+0.05(20-x)=0.10(-74) | | a-4a=35 | | 3/2=8/1 | | c/4=2 | | 13-(2x+2)=3x+2(x+2) | | 8y+144=5y-108 | | x=14+-6z | | (13x+45)=(19x+3) | | 8x-9=-3y+2 | | 2c+5=-3(c-8) | | 1.5-0.25(a+4)=3 | | x^2-18x+36=0 | | 8=10-3k | | -(5b+2)+2(4b-6)= | | x+6z=14 | | 8y+144=108-5y | | 5m-50=100 | | 4m-3m=12 | | 2(180-x)-120=30 | | 17-2x=12-(6x+3) | | -16+5x=-7(-6+8n)+3 | | 5x-3(2x+3)=3(x+11) |

Equations solver categories